2015
DOI: 10.1097/nor.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Changing Measures to Evaluate Changing Bone

Abstract: Osteoporosis is a silent, progressive disease affecting millions of Americans, costing $23.5 billion annually (). Fragility fractures, painful and costly sequelae of osteoporosis, are frequently underdiagnosed and undertreated partially because of limited assessment measures. Currently, bone mineral density measured by dual-energy x-ray absorptiometry is the surrogate marker of bone health () but has shortcomings predicting fragility fractures. Bone turnover markers and magnetic resonance spectroscopy are prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The FRAX Tool DXA alone has been identified as an unreliable fracture risk guide [40,41]. Additional fracture risk assessment algorithms like the FRAX and other tools have been developed, which, when used in conjunction with DEXA scanning, provide more accurate assessments of a postmenopausal woman's fracture risk [42].…”
Section: Fracture Risk Assessmentmentioning
confidence: 99%
“…The FRAX Tool DXA alone has been identified as an unreliable fracture risk guide [40,41]. Additional fracture risk assessment algorithms like the FRAX and other tools have been developed, which, when used in conjunction with DEXA scanning, provide more accurate assessments of a postmenopausal woman's fracture risk [42].…”
Section: Fracture Risk Assessmentmentioning
confidence: 99%
“…Research reported that ADT was significantly associated with reduced bone mineral density (BMD) in the lumbar spine, femoral neck, and total hip compared with controls (Kim et al, 2019). Nevertheless, BMD can only explain 60-80% of bone variation, and T-score is lack of complete insight on bone quality and construction (Li et al, 2004;Fitton et al, 2015). The association between fracture risk and ADT has been investigated in previous meta-analyses; however, some studies have not performed subgroup analysis based on disease state of prostate cancer, thus rendering indistinct the risks of pathological and nonpathological ADT-related fractures (Serpa Neto et al, 2010).…”
Section: Introductionmentioning
confidence: 99%